2005
DOI: 10.1111/j.1532-5415.2005.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Should Older People in Residential Care Receive Vitamin D to Prevent Falls? Results of a Randomized Trial

Abstract: Older people in residential care can reduce their incidence of falls if they take a vitamin D supplement for 2 years even if they are not initially classically vitamin D deficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
249
0
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(260 citation statements)
references
References 33 publications
(77 reference statements)
2
249
0
9
Order By: Relevance
“…A small pilot study of 21 inpatient hospice patients showed an association between vitamin D deficiency and greater functional impairment [29], and a randomized trial of vitamin D supplementation in elderly women showed improved lower limb muscle strength and mobility [30]. Many studies in the elderly [31][32][33], but not all [34], demonstrate a beneficial effect of vitamin D supplementation in reducing the incidence of falls. One study reported that higher physiological testosterone levels in older men and women may protect against falls, and that the benefit may be additive in those taking vitamin D supplementation [35].…”
Section: Discussionmentioning
confidence: 99%
“…A small pilot study of 21 inpatient hospice patients showed an association between vitamin D deficiency and greater functional impairment [29], and a randomized trial of vitamin D supplementation in elderly women showed improved lower limb muscle strength and mobility [30]. Many studies in the elderly [31][32][33], but not all [34], demonstrate a beneficial effect of vitamin D supplementation in reducing the incidence of falls. One study reported that higher physiological testosterone levels in older men and women may protect against falls, and that the benefit may be additive in those taking vitamin D supplementation [35].…”
Section: Discussionmentioning
confidence: 99%
“…In that study, however, serum 25(OH)D levels were initially higher (77 nmol l À1 ) compared with our group (36 nmol l À1 ). Other large dose calcium/ vitamin D supplementation studies in elderly residents have not documented rates of 25(OH)D deficiency (Krieg et al, 1999;Peacock et al, 2000;Grados et al, 2003) nor did they measure serum 25(OH)D at follow-up (Flicker et al, 2005;Law et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, P-controlled, double-blind trial for 2 years, among Australian aged care residents, vitamin D supplementation (ergocalciferol, initially 250 mg given once weekly and then 25 mg daily) in combination with 600 mg of calcium, reduced the rates of falls (Flicker et al, 2005); and among 84-year-old, ambulatory women, supplementation with 20 mg vitamin D 3 and 1200 mg calcium for 18 months, reduced hip fractures by 43% and total non-vertebral fractures by 32% (Chapuy et al, 1992). In a randomized, double blind, controlled trial, supplementation with folate (5 mg) and vitamin B12 (1500 mg) has been found to reduce hip fracture rates in elderly stroke patients (Sato et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Calciferol supplementation in the elderly general population has been associated with a reduction in falls and fractures as well as improvement in myopathy, including grip and lower limb strength (34)(35)(36). However, contrasting results have been reported with high-dose therapy (37).…”
Section: Muscle Strength Functional Capacity and Hrqolmentioning
confidence: 99%